Chemical characterization and bioactive properties of Geranium molle L.: from the plant to the most active extract and its phytochemicals. Issue 5 (20th April 2016) - Graça, V. C.; Barros, Lillian; Calhelha, Ricardo C.; Dias, Maria Inês; Carvalho, Ana Maria; Santos-Buelga, Celestino; Ferreira, Isabel C. F. R.; Santos, P. F.
Abstract : The phytochemical characterization, antioxidant activity and in vitro cytotoxicity against human cancer cell lines of Geranium molle L. extracts are reported for the first time. Abstract : After a period of indifference, in which synthetic compounds were favored, there is an increasing interest in the study of the biological properties of plants and the active principles responsible for their therapeutic properties. Geranium molle L. has been used in the Portuguese folk medicine for the treatment of various ailments including cancer but, unlike many of the species from the Geranium genus, its phytochemical characterization and biological activity are virtually unexplored. In this study a G. molle sample from Trás-os-Montes, north-eastern Portugal, was chemically characterized regarding nutritional value, free sugars, organic acids, fatty acids and tocopherols, and several aqueous (decoction, infusion) and organic ( n -hexane, dichloromethane, ethyl acetate, acetone, methanol) extracts of the plant were assessed for their bioactive properties. The antioxidant activity was evaluated by means of the free radicals scavenging activity, reducing power and inhibition of lipid peroxidation. The cytotoxicity of the different extracts was assessed in vitro against several human cancer cell lines (breast, lung, cervical and hepatocellular carcinomas) and, additionally, their hepatotoxicity was evaluated using a porcine liver primary cell culture. G. molle was shown to be rich in carbohydrates and proteins, providing tocopherols and essential fatty acids. Amongst the various extracts, the acetone extract was found to have the highest content of phenolic compounds (mainly ellagitannins, but also some flavone and flavonol glycosides) as well as the highest antioxidant and cytotoxic activities. To the best of our knowledge, this is the first report on the chemical composition and bioactive properties of G. molle .